Percangan Gelanggang Olahraga di Kota Tangerang Dengan Tema Arsitektur Modern - Risky Sumarauw; Anggraeni Dyah Sulistiowati; Harfa Iskandaria (MAESTRO, 2023)
The sports center is an important facility for carrying out sports activities of various kinds. For the community, especially the Tangerang City area. This final project is a means to add further ideas in the development of Tangerang City in the field of sports infrastructure design that follows the times or in other words modern. This idea also aims to optimize land for city facilities to increase the attractiveness of the city of Tangerang, especially for teenagers. The design methodology is specifically reviewed including the understanding of modern architecture, analysis of actors and activity patterns, selection of the form and characteristics of the site or structure, the shape of the room and the arrangement of the building, the mass pattern of the building, the materials in the building and the utilities of the sports arena in Tangerang City. The sports arena can be used for sports activities, futsal, basketball, volleyball, sepaktakraw and speak ball. Therefore, the design of a sports arena with the concept of modern architecture can add to the request of the people of Tangerang City for sports. Keywords: Modern Architecture, Sports Center, Facilities.